TRANSDERMAL DELIVERY OF AN EFFECTIVE NONSTEROIDAL ANTI-INFLAMMATORY DRUGS FOR PAIN MANAGEMENT IN ARTHRITIS - D, MANJULA; RAJ, ABHISHEK; JENITA J, JOSEPHINE LENO; BANU, SHANAZ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The current research work has been carried out with the aim to develop a transdermal gel formulation of fenoprofen (a nonsteroidal anti-inflammatory drug used to treat pain associated in arthritis) which would overcome the gastrointestinal-related problems associated with oral administration of the drug. The present study aims at formulating transdermal gels using different concentrations of Carbopol, hydroxypropyl methylcellulose (HPMC), sodium alginate, and guar gum. Methods: The formulated gels were subjected for various evaluation tests such as clarity, homogeneity, viscosity, drug content, pH, spreadability, and in vitro permeation studies. Drug–polymer interaction was studied by Fourier transmission infrared (FTIR) and differential scanning calorimetry (DSC). The in vitro permeation studies were performed in phosphate buffer 7.4 using Franz diffusion cell. Results: The FT-IR and DSC studies showed no chemical interaction between drug and polymers used. All the formulated gels showed acceptable physical properties with respect to clarity, homogeneity, viscosity, drug content, pH, and spreadability. Among all the gel formulations, Carbopol gels containing fenoprofen showed good drug release compared to HPMC, sodium alginate, and guar gum. Optimized formulation was further subjected to kinetic studies which showed Higuchi model of drug release. The same formulation showed significant anti-inflammatory and analgesic activity, tested in Wistar albino rats. No signs of erythema, edema, flushing, and papules were observed when skin irritation test was performed. Stability studies under accelerated condition showed satisfactory results for the optimized formulation. Conclusions: Thus, it was concluded from the results that the optimized formulation showed controlled and slow drug delivery. Animal studies were significant at p<0.05 and 0.001. The selected formulation was stable at various ambient temperatures.